Optimal postoperative delirium prediction after coronary artery bypass grafting surgery: a prospective cohort study - Ma, Ying; Sui, Dongxin; Yang, Shaozhong; Yang, Xiaomei; Oldam, Joseph; Semel, Jessica L.; Wang, Zhihao; Fang, Ningning (Frontiers in Cardiovascular Medicine, 2023)
Background: Postoperative delirium (POD) presents as a serious neuropsychiatric syndrome in patients undergoing off-pump coronary artery bypass grafting (OPCABG) surgery. This is correlated to higher mortality, cognitive decline, and increased costs. The Age-adjusted Charlson Comorbidity Index (ACCI) is recognized as an independent predictor for mortality and survival rate. The purpose of our study is to estimate the predictive value of ACCI on the POD in patients undergoing OPCABG surgery. Methods: This prospective cohort study enrolled patients undergoing OPCABG surgery between December 2020 and May 2021 in Qilu Hospital. Patients were divided into the low-ACCI group (score, 0-3) and the high-ACCI group (score ≥ 4) according to their ACCI scores. The Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) and CAM were used to diagnose POD within seven days after surgery. The general, laboratory, and clinical data of the patients were recorded and collected. The characteristic ROC curve was applied to further assess the predictive value of ACCI for POD in patients following OPCABG surgery. Results: 89 patients were enrolled, including 45 patients in the low-ACCI group and 44 patients in the high-ACCI group.Compared with the low-ACCI group, the incidence of POD was higher in the high-ACCI group (45.5%vs15.6%, P=0.003). Multivariate logistic regression analyses showed that ACCI (OR: 2.433; 95%CI: 1.468-4.032; P=0.001) was an 4 independent risk factor for POD. ACCI can predict POD in patients following OPCABG surgery accurately with the AUC of 0.738, and the Hosmer-Lemeshow goodness of fit test X 2 = 5.391, P = 0.145.The high-ACCI group showed a high incidence of POD. ACCI was an independent factor associated with POD in patients following OPCABG surgery. In addition, ACCI can predict POD accurately in patients following OPCABG surgery.